COMPARISON OF AMINO ACIDS IN 8 DIFFERENT BOILED TROPICAL FRUITS - Palaniswamy, Radha; Selvaraj, Dhanyasri; Renganathan, Sandhiya (International Journal of Current Pharmaceutical Research, 2019)
Objective: To determine the protein quality, especially the amino acid content of 8 tropical fruits both raw and boiled samples. Eight different tropical fruits were used in the study (Apricot, Jamun, Dragonfruit, Pomegranate, Mangustan, Litchi, Jackfruit, and Kiwi. Methods: Ninhydrin method was used for the estimation of the concentration of amino acids present in the above fruits. Raw and boiled fruits were used for the study. Results: Both raw and boiled forms which showed thats Jamun and Mangustan contained highest concentration amino acids whereas apricot shows the lowest concentration of amino acids except in Jamun which showed higher values in the raw fruit whereas in others the boiled samples showed higher values. Conclusion: It was evident that tropical fruits have a good balance of the essential amino acids (both raw and boiled fomr) which provide significant sources of protein in our diet.